Ocorrência de infecção por Leishmania sp. em cães no município de Florianópolis, Santa Catarina - Pacheco, Acácio Duarte [UNESP] (2013)
The aim of the present study was to investigate the occurrence of Leishmania infantum chagasi infection in 491 dogs living in Florianópolis, Santa Catarina, a region considered non-endemic for visceral leishmaniasis, but with notification of autochthonous of canine cases in 2011. The seroprevalence in this population was 0.4% (2/491) by ELISA and 4.09% (24/491) by IFAT. There was a poor agreement between the serological techniques (k = 0.069). Only one dog presented seroreactivity in both serological methods. In the same animal Leishmania sp. DNA was amplified from whole a blood sample by conventional PCR and Real- Time PCR. It was not possible to sequence the amplicons and, thereby, to determine the Leishmania specie involved. The results of this study highlight the necessity of epidemiological investigation in the county